Cerebral Oxygenation in Preterm Infants Developing Cerebral Lesions - Schwab, Angelika L.; Mayer, Benjamin; Bassler, Dirk; Hummler, Helmut D.; Fuchs, Hans W.; Bryant, Manuel B. (Frontiers in Pediatrics, 2022)
Background We investigated the association between cerebral tissue oxygen saturation (cStO2) measured by near-infrared spectroscopy (NIRS) and cerebral lesions including intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL). Methods Preterm infants <1,500 g received continuous cStO2 monitoring, initiated at the earliest time possible and recorded until 72 h of life. Mean cStO2 over periods of 5, 15, 30 min and 1 h were calculated. To calculate the burden of cerebral hypoxia, we defined a moving threshold based on the 10th percentile of cStO2 of healthy study participants and calculated the area under the threshold (AUT). cStO2 <60% for >5 min was regarded a critical event. The study was registered on clinicaltrials.gov (ID NCT01430728, URL: https://clinicaltrials.gov/ct2/show/NCT01430728?id=NCT01430728&draw=2&rank=1). Results Of 162 infants (gestational age: mean 27.2 weeks, standard deviation 20 days; birth weight: mean 852 g, standard deviation 312 g) recorded, 24/12 (14.8%/7.4) developed any/severe IVH/PVL. Mean cStO2 was significantly lower in infants with IVH/PVL as well as severe IVH/PVL. In addition, we observed critical events defined by mean cStO2 over 5 min <60% in four infants with severe IVH/PVL during NIRS monitoring. AUT showed no statistically significant difference between outcome groups. Conclusion These findings suggest that cStO2 is lower in infants developing IVH/PVL. This may be related to lower oxygenation and/or perfusion and implies that cStO2 could potentially serve as an indicator of imminent cerebral lesions.